Pengaruh Financial Knowledge, Financial Attitude dan Income Terhadap Financial Behaviour - Robiah, Rina Siti; Ridwan (Economic Reviews Journal, 2025)
The research findings discuss how financial knowledge, financial attitude, and income empirically impact the financial behavior of private employees in Bandung Regency. The quantitative method is used as the research method with both descriptive and verificative approaches. Respondent data was collected from 100 private employees in Bandung Regency by distributing questionnaires and using multiple linear regression as the research analysis method. With the function to determine the simultaneous and partial effects of the variables financial knowledge, financial attitude, and income on the variable financial behaviour. The findings from variables X1 and X2 have a positive impact with appropriate significance, but variable X3 does not affect Y. Simultaneous findings indicate that all variables X1, X2, and X3 have a significant impact on financial behavior. The r2 value of 0.354 means that the three variables only account for 35.4% in influencing financial behavior, while the remaining 64.6% is related to other variables